Relationships between Malaysians Cultivars of Tongkat Ali (Eurycoma longifolia Jack) Obtained through RAPD Analysis - Razi, Aishatur Radhiah Mohd; Abdul-Aziz, Azila; Alwee, Sharifah Shahrul Bariah Syed; Aziz, Ramlan (International Journal of Biotechnology for Wellness Industries, 2013)
Random Amplified Polymorphic DNA (RAPD) analysis was done on Eurycoma Longifolia Jack (ELJ) cultivars originating from 7 different locations in Malaysia to determine whether the originality of ELJ cultivars can be preserved in an uncontrolled cultivation area. Out of 60 arbitrary 10-mer primers, a total of 320 DNA fragments were amplified with an average of 53.3 RAPD markers per primer. 71 (22%) of the 320 DNA-fragments was found to be monomorphic. The remaining 249 (78%) were polymorphic. The approximate size of the largest fragment produced was 3000 base pair (bp) and the easily recognizable fragment produced was 300 bp. Similarity index of RAPD banding patterns was used to investigate the relationships between ELJ cultivars. Mantel test showed that the correlation between Jaccard and Dice similarity matrices was high and significant (0.9907). The dendogram showed that ELJ cultivars can be clustered into three main clusters. Cluster 1 consisted of Sabah cultivars (East Malaysia), Cluster 2 consisted of Pahang and Terengganu cultivars (middle part of West Malaysia) while cluster 3 consisted of Kedah and Kelantan cultivars (east part of West Malaysia). The results of Principle Coordinates Analysis (PCA) were comparable to the Dendogram by UPGMA. The first two principle coordinates explained 53.62% of total variations and separated the 37 ELJ cultivars into three main clusters with a slight overlap between each other.